2010
DOI: 10.1063/1.3490133
|View full text |Cite
|
Sign up to set email alerts
|

Ionic relaxation in polyethyleneimine-lithium bis(trifluoromethylsulfonyl) imide polymer electrolytes

Abstract: Polymer electrolytes containing polyethyleneimine and different concentrations of lithium bis͑trifluoromethylsulfonyl͒ imide were investigated by impedance spectroscopy at different temperatures. Two equivalent circuit models were compared for the bulk impedance response. The first one includes a conductive Havriliak-Negami ͑HN͒ element which represents ionic conductivity and ion pair relaxation in a single process, and the second model includes a dielectric HN element, which represents ion pair relaxation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…It is observed that ε′ of the electrolytes is higher than that of pristine PEO throughout the frequency range; however, the rate of increase at higher loading is diminished. The observed increase in ε′ with the salt loading is consistent with the effective medium theory wherein the enhancement of dielectric constant (ε′) is attributed to the addition of salt having relatively higher dielectric constant 70 compared to polymer matrix. The imaginary part (ε″) of the permittivity is also observed to increase with the salt loading as shown in Figure 3b.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…It is observed that ε′ of the electrolytes is higher than that of pristine PEO throughout the frequency range; however, the rate of increase at higher loading is diminished. The observed increase in ε′ with the salt loading is consistent with the effective medium theory wherein the enhancement of dielectric constant (ε′) is attributed to the addition of salt having relatively higher dielectric constant 70 compared to polymer matrix. The imaginary part (ε″) of the permittivity is also observed to increase with the salt loading as shown in Figure 3b.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…The single-ion conductor can overcome these challenges faced by salt-doped counterparts. Previous studies indicate that high ionic dissociation and enhancement in the concentration of charge carriers can be achieved by introducing nitrogen atoms into the backbone of the polymer, which is known to decrease the anion–cation binding energies. , The anions of the polymer precursors (Li x PON and Li x SiPON) are proposed to be chemically bound with the PEO polymer backbone, resulting in only cation transport. The anionic units in these polymer precursors/PEO mixtures are predicted to be immobile in regard to conductivity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Frequency response data sets for a polymer electrolyte containing polyethylene imine (PEI) and lithium bis(trifluoromethylsulfyl imide (LiTFSI) were kindly supplied by Professor G. A. Niklasson . They have been discussed by him and his group in ref . Here we consider the data set with a [N]:[Li] molar ratio of 400:1 at 20 °C and fit it with different models than those utilized in ref .…”
Section: Experimental Data Fitsmentioning
confidence: 99%